2016
DOI: 10.1093/ee/nvw110
|View full text |Cite
|
Sign up to set email alerts
|

Frugivory by Brown Marmorated Stink Bug (Hemiptera: Pentatomidae) Alters Blueberry Fruit Chemistry and Preference by Conspecifics

Abstract: The brown marmorated stink bug, Halyomorpha halys (Stål), is an invasive pest from Asia that feeds on many agricultural crops in the United States, including blueberries. Yet, the effects of H. halys feeding on fruit chemistry and induced resistance to insects remain unknown. Here we hypothesized that frugivory by H. halys changes fruit chemical composition, which in turn affects insect feeding behavior. In field experiments, blueberry fruit was either mechanically injured or injured by 0 (control), 2, 5, or 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 44 publications
4
7
1
Order By: Relevance
“…Glucose also serves as a signaling molecule in plants and can increase in abiotically and biotically stressed plants [22,23]. In this study, the stink bug increased the total sugar content in the apples, which is in contrast to Zhou et al [24], who reported no noticeable reduction in sugar content between infested and uninfested blueberries.…”
Section: Sugarscontrasting
confidence: 86%
“…Glucose also serves as a signaling molecule in plants and can increase in abiotically and biotically stressed plants [22,23]. In this study, the stink bug increased the total sugar content in the apples, which is in contrast to Zhou et al [24], who reported no noticeable reduction in sugar content between infested and uninfested blueberries.…”
Section: Sugarscontrasting
confidence: 86%
“…Additionally, this may also include gustatory cues because H. halys often probes into host plants (Wiman et al ., ). Furthermore, feeding by H. halys induces changes in the nutritional quality of some plants, making them less preferred by conspecifics afterwards (Zhou et al ., ), suggesting an important role for fruit gustatory and volatile cues.…”
Section: Discussionmentioning
confidence: 99%
“…With its large number of host plants, from ornamental plants to fruit and vegetable plants, it causes serious damage to agriculture in Europe and North America [8]. It causes damage to fruit such as apples, blueberries, etc., making them inedible for humans [9]. Several things have helped this pest to become so successful in spreading across the world, including climate change, lack of natural predators, and global trade [10].…”
Section: Introductionmentioning
confidence: 99%